Hidden messages in fluids: A review of clinical and fundamental perspectives on post‐lymph node dissection drains - Mak, Chon‐Hou; Wang, Guang‐Rui; Li, Zi‐Zhan; Cao, Lei‐Ming; Zhang, Chen‐Xi; Zhu, Zhao‐Qi; Liu, Bing; Bu, Lin‐Lin (International journal of cancer, 2025)
In recent years, there has been a growing interest in liquid biopsy due to its non‐invasive diagnostic value. Postoperative drainage fluid (PDF) is the fluid exudate from the wound site following lymph node dissection. PDF is regarded as a medical waste with no specific clinical significance. Nevertheless, the liquid biopsy of PDF may enable the reuse of this fluid. PDF contains a variety of body fluids, including blood and lymph. PDF contains a variety of biological components, including cytokines, extracellular vesicles (EVs), proteins, nucleic acids, cells and bacteria. These components are indicative of the postoperative inflammatory response, the immune response and the therapeutic response. In this review, we examine the current state of research in the field of liquid biopsy in PDF, elucidating how the analysis of its components can assess the prognosis of patients after lymph node dissection, monitor real‐time changes in patient status, and identify new biomarkers and potential therapeutic targets.